First Ring‐Expanded Maytansin Lactone Accessed by a New Mutasynthetic Variant - Wesemann, Friederike (Chembiochem, 2020)
A multiblocked mutant strain (ΔAHBA and Δasm12, asm21) of Actinosynnema pretiosum, the producer of the highly toxic maytansinoid ansamitocin, has been used for the mutasynthetic production of new proansamitocin derivatives. The use of mutant strains that are blocked in the biosynthesis of an early building block as well as in the expression of two tailoring enzymes broadens the scope of chemo‐biosynthetic access to new maytansinoids. Remarkably, a ring‐expanded macrolactone derived from ansamitocin was created for the first time.